Comprehensive oral treatment of drooling factors in patients with neonatal asphyxia and diagnosed with DDH: Case report - Wita Puspitasari; Intan Maulani; Niekla Survia Andiesta; Meirina Gartika (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACT Introduction: Drooling is salivary incontinence or involuntary spillage of saliva onto the lower lip due to anterior sialorrhea and oral motor dysfunction. The instability of the hip region in this patient causes the body posture to become less aligned, this condition may affect the oral motor. Rampant caries causes sialorrhea which also exacerbates drooling in these patients. Aim of this case report is to report comprehensive oral treatment in drooling child patients with neonatal asphyxia and diagnosed with developmental dysplasia of the hip (DDH). Case Report: A 6-year-old girl patient was brought by her mother to the Pediatric Dental Clinic at Al Ihsan West Java Provincial Hospital with concerns of excessive salivation and frequent toothache. Clinical examination revealed multiple caries. The patient was diagnosed with DDH resulting in poor posture attributed to hip bone dysplasia. The comprehensive dental treatment, performed under general anesthesia, encompassed various procedures such as pulpectomy, Stainless Steel Crown (SSC), Strip crown with Glass Ionomer Cement (GIC) restoration, fissure sealant, topical fluoride treatment, and extraction. During the one-week recall, there were no complaints of pain and decreased drooling. The patient was referred to the medical rehabilitation department for further treatment of swallowing problems. The patient is still undergoing DDH treatment with an orthopedic specialist at Santosa Hospital, Bandung. Conclusion: Comprehensive oral treatment and orthopedic treatment are ways to reduce drooling factors in patients who have a history of neonatal asphyxia and are diagnosed with DDH. Multidisciplinary cooperation in both dentistry and general medicine is needed so that major problems are resolved and children's quality of life is improved.Keywords Comprehensive oral treatment, drooling factors, neonatal asphyxia, developmental dysplasia of the hip (DDH)Perawatan oral komprehensif faktor drooling pada pasien asfiksia neonatorum dan terdiagnosis DDH: Laporan kasusABSTRAK Pendahuluan: Drooling adalah inkontinensia saliva atau tumpahan saliva yang tidak disengaja ke bibir bawah karena sialorrhea anterior dan disfungsi motorik mulut. Instabilitas daerah pinggul pada pasien ini menyebabkan postur tubuh menjadi kurang selaras sehingga berpengaruh terhadap motorik oral. Karies rampan menyebabkan sialorrhea yang juga memperparah drooling pada pasien ini. Tujuan dari laporan kasus ini adalah untuk melaporkan perawatan oral yang komprehensif pada pasien anak yang drooling dengan asfiksia neonatal dan didiagnosis displasia perkembangan pinggul (DDH). Laporan Kasus: Pasien anak usia 6 tahun dibawa ibunya ke Klinik Gigi Anak di RSUD Al-Ihsan dengan keluhan mengeluarkan saliva berlebih dan sering sakit gigi. Hasil pemeriksaan klinis didapatkan karies hampir pada seluruh gigi. Pasien didiagnosis dengan Displasia Perkembangan Pinggul (DDH) yang mengakibatkan postur tubuh yang buruk yang dikaitkan dengan displasia tulang pinggul. Perawatan gigi yang komprehensif, dilakukan dengan anestesi umum, meliputi berbagai prosedur seperti pulpektomi, Stainless Steel Crown (SSC), restorasi Strip crown dengan Glass Ionomer Cement (GIC), fissure sealant, perawatan fluoride topikal, dan ekstraksi. Saat kontrol satu minggu, tidak ada keluhan sakit dan drooling berkurang. Pasien dirujuk ke bagian rehabilitasi medik untuk dilakukan perawatan lanjutan pada masalah penelanan. Pasien masih melakukan perawatan DDH dengan dokter spesialis ortopedi di RS Santosa Bandung. Simpulan: Perawatan komprehensif rongga mulut dan perawatan ortopedi merupakan salah satu cara untuk mengurangi faktor penyebab drooling pada pasien yang memiliki riwayat asfiksia neonatorum dan didiagnosa DDH. Kerjasama multidisiplin baik dalam bidang spesialisasi kedokteran gigi maupun dalam bidang spesialisasi kedokteran umum diperlukan agar masalah utama teratasi dan kualitas hidup anak menjadi lebih baik.Kata kunci Perawatan oral komprehensif; faktor drooling; asfiksia neonatal; developmental dysplasia of the hip (DDH)